Merdeka Belajar Curriculum: EFL Teachers’ Preparations and Practices at Sekolah Penggerak Kota Jambi - Nyimas Triyana Safitri; Arani Tri Ananda; Masbirorotni Masbirorotni (Scope : Journal of English Language Teaching, 2023)
This study aimed to explore EFL teachers’ preparation and implementation for the inclusion of English course in Junior High School at Program Sekolah Penggerak. A qualitative method was applied in this study. To obtain the data in this study, a semi-structured interview and observation were employed. The interview was conducted with 5 English teachers at different junior high schools in Jambi city. Then, the observations were conducted with the teachers after the interview session. The data were analyzed by using 3 sequences phases; data condensation, data display, and drawing conclusions. The result of this study revealed the preparation of teachers in teaching was in form of training, teachers’ development, facilities, and material for teaching. However, Merdeka Belajar Curriculum has been implemented by teachers which had been through the analysis of the learning achievements, implementation of diagnostic assessment, and development of teaching modules, implementation of differentiation learning, teaching evaluation and assessment. As finding presented, this study provides the implication in pedagogy such as the reference for future researchers and for improvements in the implementation of English language learning.